2013
DOI: 10.1177/1082013213488381
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on wheat dough rheology and wheat protein solubility

Abstract: In the present study, the influence of moisture content, temperature and time during heat treatment of wheat flour was investigated. Heat treatment was carried out on laboratory scale in a water bath at 50-90 degrees C for times up to 3 h. Flour functionality was evaluated by analysing protein solubility in acetic acid as well as by the formation of bread-like doughs, which were then analysed with dynamic oscillatory and rotational rheometry. Effects during heat treatment were explained on a molecular level us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 15 publications
4
40
0
Order By: Relevance
“…Dough stability during prolonged mixing has commonly been considered to be a factor of gluten quality. Generally, the HMT processes cause lower network strength of dough and thus significant deterioration in the mixing properties such as DDT and dough stability due to the gluten protein denaturation, similar results had been observed by Mann et al (2013) and Bucsella et al (2016). Heat-moisture treatment had a significant effect on the mixing behaviors of germinated wheat flour, both treated in form of kernel and flour.…”
Section: Mixolab Behaviorssupporting
confidence: 68%
See 2 more Smart Citations
“…Dough stability during prolonged mixing has commonly been considered to be a factor of gluten quality. Generally, the HMT processes cause lower network strength of dough and thus significant deterioration in the mixing properties such as DDT and dough stability due to the gluten protein denaturation, similar results had been observed by Mann et al (2013) and Bucsella et al (2016). Heat-moisture treatment had a significant effect on the mixing behaviors of germinated wheat flour, both treated in form of kernel and flour.…”
Section: Mixolab Behaviorssupporting
confidence: 68%
“…After germination, the weakening increased obviously, indicating a decrease in the sensitivity of the dough to overmixing (Lorenz, Roewe-Smith, Kulp, & Bates, 1983). Bucsella et al (2016) conducted their experiments at 95°C for 5 min using a retention screws by a continuous process (5-20 L/ hr water), while Mann et al (2013) performed their HMT process through a water bath at 90°C for longer time (30 min), with moisture content of 16.0%-17.0%, which was closer to conditions used in this study. Thus, damage to the gluten during germination was a probable explanation for the increased weakening.…”
Section: Mixolab Behaviorsmentioning
confidence: 89%
See 1 more Smart Citation
“…CFth and BFth had higher C2 values and had lower weakening compared to that of the untreated ones. This observation contradicts the findings of Mann, Schiedt, Baumann, Conde-Petit, and Vilgis (2013). In their study dry heat treated (50-90°C up to 3 h) cake flour showed lower gluten strength due to heat-induced gluten agglomeration that was expressed in low network strength after a longer tempering period.…”
Section: Effects Of Dry and Hydrothermal Treatments On Gluten Propertiesmentioning
confidence: 55%
“…In addition, the observed increase in the WA value is related to the higher water uptake of starch granules, as a consequence of the cross‐linked protein network loss surrounding them. Protein aggregation and starch surface modifications after heat treatment lead to changes in starch–protein and starch–starch interactions, also affecting the rheological properties of doughs (Mann, Schiedt, Baumann, Conde‐Petit, & Vilgis, ).…”
Section: Resultsmentioning
confidence: 99%